The impact of social isolation on rat behaviour - Porkess, Malini Veronica (2008)
Schizophrenia is a psychiatric disorder with symptoms including delusions, social withdrawal and cognitive deficits. The cognitive symptoms respond poorly to current antipsychotic medication and in order to develop new treatments it is necessary to model these deficits in animals. Rearing rats in isolation from weaning causes behavioural, cognitive and neurochemical alterations, some of which have relevance to the symptoms of schizophrenia. The work described in this thesis aimed to further characterise the behavioural and cognitive changes found isolation reared rats.